Linkages between PISA Results and E-Working - Hvorecký, Jozef; Beňo, Michal (Emerging Science Journal, 2021)
The PISA tests are considered as a quality measurement for education. If it is so, then their high results might influence the proportion between blue and white collars. As the intellectually demanding functions can be more easily executed over the internet, in a long term, this fact should be reflected in a growing proportion of e-working. To study this assumption, we examine adopting e-working within selected thirty-five countries. Research questions were formed as follows: Is there a demonstrable influence of favorable PISA results on the overall rates of e-working in certain states? Is it possible to sustain different components with e-working? Can appropriate e-working legislation contribute to the overall rates of e-working at a state’s level? Our study adopted Spearman’s Rho correlation using 4 numerical variables to measure the strength of association between pairs of variables – the proportion of e-working and four country’s PISA averages in Mathematics, Science, Reading and Financial Literacy. Its results indicate a positive correlation: the probability of e-working increases with the PISA results growth. Further, Qualitative Content Analysis was used. Based on our data e-working will not go away and it is time to update law on e-working. Governments should formalize rights and duties. Face-to-display work is likely to be an unstoppable evolution at workplace. These components affected higher e-workability. These results draw attention to how e-working is becoming major element in common life with some challenges and difficulties and that we need to study these two influencer factors in order to optimize its arrangements. Doi: 10.28991/esj-2021-01277 Full Text: PDF